Proposta de rede para postos de GNV no Maranhão através de otimização espacial - BARBOSA, Luciana Pereira (2024)
Natural gas has applications in various sectors. Maranhão is currently one of the few states with active onshore production and 7.1% of the country's exploratory blocks within its boundaries. The current natural gas sector in Brazil faces infrastructure shortages, but new transportation methodologies, such as virtual pipelines, present a promising opportunity for the interiorization of Natural Gas (NG). In this perspective, natural gas demand strategies in Maranhão, where there is still no pipeline network, are extremely important to foster demand, production, and regional development. Among fossil fuels, natural gas offers environmental and health benefits, presenting itself as a promising alternative to diesel in the transportation sector. The creation of routes for supplying Compressed Natural Gas (CNG) along highways is part of a recent approach, known as Blue Corridors. The assumption behind the creation of this infrastructure in the state relies on the following points for Maranhão: there is NG production, the Port of Itaqui as an input and output gateway, high grain production, and the presence of large industries. Thus, this energy source, such as CNG used in the transportation sector in Maranhão, can establish new scenarios for the state's transportation matrix, favoring a gradual change in the sector and reducing external fuel dependency. Benefiting from technological advances, applying spatial optimization techniques, this study aimed to provide network scenarios through optimal allocation of CNG station points in the state of Maranhão, offering an uninterrupted CNG network configuration. The importance of using georeferenced data for resource allocation research acquired from public databases enabled the creation of databases for future research, offering possible network configurations for CNG corridors in Maranhão. Using spatial optimization techniques, this study developed network configurations for CNG distribution in the state of Maranhão, focusing on the most developed municipalities. The results demonstrate that the strategic location of optimized points for the installation of CNG stations plays a crucial role in promoting efficient and comprehensive natural gas distribution. These network configurations have the potential to meet transportation demands, stimulate regional development, and reduce external fuel dependency in the state. Additionally, the study emphasizes the importance of using georeferenced data for resource allocation research, highlighting the viability of its acquisition in public databases for the creation of databases for future research. These results contribute to informing policies and strategies for expanding CNG infrastructure, benefiting the economy, the environment, and society in Maranhão.